2012
DOI: 10.1097/shk.0b013e31826660f2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peroxynitrite in Sepsis-Induced Acute Kidney Injury in an Experimental Model of Sepsis in Rats

Abstract: The mechanisms involved in sepsis-induced acute kidney injury (AKI) are unknown. We investigated the role of nitrosative stress in sepsis-induced AKI by studying the effects of manganese (III) tetrakis-(1-methyl-4-pyridyl) porphyrin pentachloride (MnTMPyP), a peroxynitrite decomposition catalyst, and aminoguanidine (AG), a selective nitric oxide synthase 2 (NOS2) inhibitor and peroxynitrite scavenger, on kidney function of rats subjected to cecal ligation and puncture (CLP). Sprague-Dawley rats (weighing 350 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
4
29
0
4
Order By: Relevance
“…Oxidative stress (oxidant/antioxidant imbalance) also plays an important role in the pathophysiology of sepsis. Previous human and animal studies confirmed severe oxidative stress in patients with sepsis, demonstrating increased oxidant markers and decreased antioxidant capacity [11][12][13][14][15][16]. Our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…Oxidative stress (oxidant/antioxidant imbalance) also plays an important role in the pathophysiology of sepsis. Previous human and animal studies confirmed severe oxidative stress in patients with sepsis, demonstrating increased oxidant markers and decreased antioxidant capacity [11][12][13][14][15][16]. Our results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…Mitochondrial oxidant generation in septic AKI plays an important role in renal tubular injury during sepsis, manifested as ischemic injury. 15,16,[35][36][37] Interestingly, mitochondria-targeted antioxidants could attenuate CLP-induced AKI, independent of systemic blood pressure. 17 Our findings showed that TLR9 deficiency helped to prevent renal mitochondrial injury and the subsequent decrease in renal function after CLP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reactive nitrogen species (RNS) is involved in sepsis-induced acute kidney injury [15,16]. Several studies showed that antioxidants alleviated sepsis-induced acute kidney injury [17,18].…”
Section: Introductionmentioning
confidence: 99%